Solid-liquid extraction of cellulases from fungal solid-state cultivation in a packed bed bioreactor - de Oliveira, Samuel Pratavieira (2020)
Cellulases are enzymes required for the production of second-generation ethanol (E2G) via biochemical route. The current paper reports the development of an apparatus for solid-liquid extraction of cellulases from solid-state fermentation (SSF) carried out in a packed bed bioreactor (PBB), operated as batch and as semicontinuous. The case study was the cultivation of Myceliophthora thermophila I-1D3b on sugarcane bagasse (SCB) and wheat bran (WB) (7: 3 w/w). The current work integrates the PBB to the first downstream step for recovering the enzymes produced by SSF. The substrate was inoculated and packed into the modules that composed the PBB. The fermentation occurred at 45 °C and air was supplied with flow rate of 350 L/h. At the end of the cultivations, each module was placed in an extraction column, a dynamic closed system in which distilled water was circulated and made to percolate the cultivated material. Variables tested were volume of water per mass of substrate, water flow rate and time of percolation. Higher contact time (120 min) and higher flow rate (2.4m3/h) allowed us to recover up to 85% of total enzyme activity by percolation. Lower volume (20mL/g) provides higher titer extract. The apparatus showed to be promising for SSF downstream, mainly for semicontinuous operation of PPBs.